Continuous positive airway pressure to avoid intubation in SARS-CoV-2 pneumonia: a two-period retrospective case-control study. Issue 2 (13th August 2020) - Oranger, Mathilde; Gonzalez-Bermejo, Jésus; Dacosta-Noble, Philippine; Llontop, Claudia; Guerder, Antoine; Trosini-Desert, Valery; Faure, Morgane; Raux, Mathieu; Decavele, Maxens; Demoule, Alexandre; Morélot-Panzini, Capucine; Similowski, Thomas
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can cause severe pneumonia requiring invasive mechanical ventilation [1], in the context of atypical acute respiratory distress syndrome (ARDS) [2]. The magnitude of the epidemic places an unprecedented pressure on intensive care units (ICUs), making avoidance of intubation a critical issue. COVID-19 pneumonia can be life-threatening. Given the unprecedented burden placed on ICU resources by the epidemic, avoiding intubation is a major issue. This study suggests that CPAP can achieve this objective. https://bit.ly/2X4Q8Zj